Perbandingan Efektivitas Antipiretik dan Analgesik Dua Merek Dagang Parasetamol dan Produk Generik Terhadap Mencit (Mus Musculus) Jantan - Cinthya Ratna Yuniar; Nasruhan Arifianto; Dian Nita Triana (STIKES Rumah Sakit Anwar Medika, 2022)
Antipyretics and analgesics are drugs that can suppress or reduce the increase in body temperature and suppress pain by inhibiting COX. In the market, branded products are often considered to have a higher quality than generic products, and patients are often found who are fanatical about one of these trademarks. Even though the products on the market have been tested for the quality of these products. Therefore, a study was conducted to compare the antipyretic and analgesic effectiveness of branded paracetamol at a higher price with branded paracetamol at a generic price (cheap) and generic paracetamol in mice induced by fever and induced pain. Experimental animals in this study used male mice (Mus musculus). The stages of antipyretic research are giving treatment to experimental animals before being treated, mice are measured rectal temperature (initial temperature), then injected with 5% peptone subcutaneously. One hour later the rectal temperature was measured again, after which the mice were treated with the test material and negative control. To test the effectiveness of analgesics, a chemical stimulation method was used which was carried out on male mice (mus musculus) given the pain-inducing compound acetic acid 0.6% (writhing test). The antipyretic test results obtained in the form of the percentage of the antipyretic power of branded paracetamol at an expensive price, branded paracetamol at a generic price (cheap) and paracetamol generic products at 0.86%, 1.07% and 0.41%, respectively, at the minute to minute observation. -60. The most effective antipyretic effect of paracetamol used to reduce the rectal temperature of febrile mice was brand B paracetamol and the lowest effectiveness was found in generic paracetamol. The analgesic effectiveness test in this study showed that there was a significant difference in analgesic effectiveness from each test group. The greatest analgesic effectiveness occurred in brand A paracetamol products with % pain inhibition in a total of 20 minutes by 47.37% and the smallest analgesic effectiveness occurred in generic paracetamol products with % pain inhibition in a total time of 20 minutes by 38.05%.